Extinguishing fires at metallurgical and mechanical engineering enterprises - Tverdokliebova, N. Ye.; Ponomarenko, O. I. (Національний технічний університет "Харківський політехнічний інститут", 2024)
In the conditions of advanced growth of machine building development, the issues of fire safety are especially acute. Fires at metallurgical and mechanical engineering most often occur in basements of machine rooms, cable rooms, oil cellars, and on combustible surfaces.
Keywords: fire safety; source of combustion; fire spreading; evacuation